The effect of service quality and customer satisfaction on Bank customer service loyalty - Aditya Yudanegara (Institute of Computer Science (IOCS), 2023)
Currently all over the world, both for consumer goods, manufactured goods, and service goods are facing the most difficult times in world history, namely the increasingly tight competition that hit all sectors, both the government sector, the private sector, the domestic sector and the foreign sector. country and other sectors that can be cross-sectoral or multi-sectoral. For this reason, this research will examine the extent to which Service Quality is one of the variables that can influence efforts to increase Customer Satisfaction and the extent to which Customer Satisfaction influences the achievement of Bank customer Service Loyalty so that in the end PT. BJB TBK Bandung can be better prepared and can win the competition that occurs. The Service Quality variables studied are Assurance, Reliability, Responsiveness, Empathy, and Tangible. This research is a descriptive-vericative research by distributing questionnaires to 105 respondents. Sampling was carried out using a probability-based sampling method in the form of convenience sampling where information and data can be obtained quickly, easily and inexpensively. While the method of data analysis uses several regression models which are analyzed by factor analysis and processed with SPSS version 25. From the results of the study it is known that service quality has an effect on customer satisfaction, and customer satisfaction has a greater effect on service loyalty. It was also found in this study that of the five dimensions of service quality,of which had the greatest impact: Perception. While the lowest impact: security